Bibliometric Analysis of Developing Sustainable Cities by Enforcement of Environmental Policies - Amponsah, Maxwell; Enok, Maryani; Nandi, Nandi (Indonesian Journal of Geography, 2025)
This bibliometric analysis explores the scholarly background surrounding the development of sustainable cities through the enforcement of environmental policies. The study aims to provide a comprehensive overview of the existing body of literature on this subject, identifying key trends, relevant authors, and thematic clusters that have contributed to the scholarly dialogue on this topic. Through a bibliometric analysis of relevant academic publications, this research seeks to discover patterns and insights that have contributed to a deeper understanding of the evolution of research in this critical realm. The research question underlying this bibliometric literature review is how can cities develop sustainably through the enforcement of environmental policies? The formulation of the research question necessitates the objectives of the study. The objectives of this research are to: assess the volume and growth of literature addressing sustainable urban development through environmental policy enforcement, identify research works and influential authors shaping the scholarly conversation on this topic, uncover thematic clusters and the interdisciplinary nature of research in developing sustainable cities through environmental policies and identify research gaps to guide future direction of research. The study employs bibliometric techniques, including citation analysis, co-authorship analysis, and term co-occurrence analysis. Preliminary findings indicate a growing interest in the intersection of sustainable urban development and environmental policy enforcement. The analysis identifies key publications that have significantly influenced the field, along with prominent authors and collaborative networks. This bibliometric analysis provides a systematic overview of the scholarly contributions to the development of sustainable cities through environmental policy enforcement.Received:2024-02-20 Revised:2024-02-29  Accepted: 2025-03-07 Published: 2025-04-27